Stresses in Viscoelastic Sphere Dried Convectively - Banaszak, J.; Kowalski, S.J. (Engineering Transactions, 2000)
The deformations and the drying-induced stresses in a saturated porous elastic and visco-elastic sphere dried convectively are analysed. The considerations are confined to the constant drying rate period. The solution of the problem is obtained using both the Laplace transformations and the numerical finite difference method. The drying experiment was performed on spheres made of three different clay sorts in order to validate the results obtained by numerical analysis. The results obtained are presented in graphical form.